2010
DOI: 10.1074/jbc.m109.090845
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Erythrocytes in Adenosine Monophosphate Initiation of Hypometabolism in Mammals

Abstract: Biochemical and mechanistic aspects into how various hypometabolic states are initiated in mammals are poorly understood. Here, we show how a state of hypometabolism is initiated by 5-AMP uptake by erythrocytes. Wild type, ecto-5-nucleotidase-deficient, and adenosine receptor-deficient mice undergo 5-AMP-induced hypometabolism in a similar fashion. Injection of 5-AMP leads to two distinct declining phases of oxygen consumption (VO 2 ). The phase I response displays a rapid and steep decline in VO 2 that is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 26 publications
8
60
1
Order By: Relevance
“…As indicated previously, the depth of the hypometabolic response is dependent on the Tb-Ta convective efficiency (section 2.2). This is further supported by the extent of the drop in Tb that is observed in 5'-AMP-treated mice, which is proportional to the difference between Tb and Ta (i.e., lower Tas induce a greater drop in Tb), demonstrating the Tb-Ta dependency [76].…”
Section: Adenosine Monophosphatesupporting
confidence: 52%
See 2 more Smart Citations
“…As indicated previously, the depth of the hypometabolic response is dependent on the Tb-Ta convective efficiency (section 2.2). This is further supported by the extent of the drop in Tb that is observed in 5'-AMP-treated mice, which is proportional to the difference between Tb and Ta (i.e., lower Tas induce a greater drop in Tb), demonstrating the Tb-Ta dependency [76].…”
Section: Adenosine Monophosphatesupporting
confidence: 52%
“…The putative contention is that intraperitoneal administration of high 5'-AMP concentrations (e.g., 500 mg/kg) lead to extensive 5'-AMP uptake by erythrocytes [79], after which the high intracellular levels of 5'-AMP drive the adenylate equilibrium (ATP + AMP  2 ADP) towards production of ADP, thereby depleting erythrocyte ATP levels [76,77]. As a result, erythrocyte 2,3-disphosphoglycerate is upregulated, limiting the binding of oxygen to hemoglobin's oxygen binding sites (referred to as oxygen affinity hypoxia) [76]. In addition to the already impaired oxygen transport, the severe cardiovascular depression following 5'-AMP administration has the potential to further exacerbate this hypoxic state (referred to as circulatory hypoxia) [78].…”
Section: Adenosine Monophosphatementioning
confidence: 99%
See 1 more Smart Citation
“…For example, hypothermia produced by N 6 -R-phenylisopropyladenosine was only partially attenuated in the Adora1 2/2 mouse (Yang et al, 2007). Also, hypothermia from high dose AMP was attributed to erythrocyte uptake of intact AMP, and this hypothermia was intact in mice lacking any one of the four adenosine receptors (Daniels et al, 2010). Most informative is the observation that N 6 -Rphenylisopropyladenosine-induced hypothermia was attenuated in adenosine A 3 receptor (A 3 AR) null (Adora3 2/2 ) mice, directly implicating the A 3 AR's involvement in hypothermia (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…When administered at a sufficient dose, 5′-AMP allows nonhibernating mammals to rapidly undergo reversible and safe severely hypothermic reactions at ambient temperatures (ATs) of 15-16°C [9][10][11][12][13]. Recently, studies have shown that hypothermia induced by 5′-AMP has an anti-inflammatory effect [10,11,14].…”
Section: Introductionmentioning
confidence: 99%